Assessing the economic value of maintained improvements in Type 1 diabetes management, in terms of HbA1c, weight and hypoglycaemic event incidence. Issue 5 (28th February 2018) - McEwan, P.; Bennett, H.; Bolin, K.; Evans, M.; Bergenheim, K.
Abstract: Aims: Insulin therapy is indicated for people with Type 1 diabetes mellitus; however, treatment‐related weight gain and hypoglycaemia represent barriers to optimal glycaemic management. This study assessed the health economic value of maintained reductions in HbA1c, BMI and hypoglycaemia incidence among the UK Type 1 diabetes population. Methods: The Cardiff Type 1 Diabetes Model was used to estimate lifetime costs, life‐years and quality‐adjusted life‐years (QALYs) for individuals with Type 1 diabetes at different baseline HbA1c, BMI and hypoglycaemic event rates. Results were discounted at 3.5%, and the net monetary benefit associated with improving Type 1 diabetes management was derived at £20 000/QALY gained. Per‐person outputs were inflated to national levels using UK Type 1 diabetes prevalence estimates. Results: Modelled subjects with an HbA1c of 86 mmol/mol (10.0%) were associated with discounted lifetime per‐person costs of £23 795; £12 649 of which may be avoided by maintaining an HbA1c of 42 mmol/mol (6.0%). Combined with estimated QALY gains of 2.80, an HbA1c of 42 mmol/mol (6.0%) vs. 86 mmol/mol (10.0%) was associated with a £68 621 per‐person net monetary benefit. Over 1 year, unit reductions in BMI produced £120 per‐person net monetary benefit, and up to £197 for the avoidance of one non‐severe hypoglyceamic event. Conclusions: Maintained reductions in HbA1c significantly alleviate the burden associated with Type 1 diabetes in the UK. Given the influence of weight and hypoglycaemia on health economic outcomes, they must also be key considerations when assessing the value of Type 1 diabetes technologies in clinical practice. What's new?: This study demonstrated the burden of inadequate Type 1 diabetes management, and quantified the value of reducing HbA1c, weight and hypoglycaemia frequency among the UK Type 1 diabetes population. Significant cost savings, quality‐adjusted life‐year gains and net monetary benefit were predicted in those who achieve HbA1c targets recommended in national guidelines; nevertheless, any incremental improvement in glycaemic management substantially reduced the burden of Type 1 diabetes mellitus on individuals and healthcare systems. Given the influence of weight and hypoglycaemia on health economic outcomes, these factors should also be key considerations when assessing the value of Type 1 diabetes technologies.